Overcoming NK-mediated rejection by anti-3rd-party central memory veto CD8 T cells through downregulation of DNAM-1 on alloreactive NK cells - Wei-Hsin Liu; Aloukick Kumar Singh; Christa Blagdon; Sandeep Kumar Yadav; Einav Shoshan; Esther Bachar-Lustig; Yair Reisner (Cell Reports)
Summary: Anti-3rd-party central memory veto CD8 T (veto Tcm) cells can overcome T cell-mediated graft rejection under mild conditioning without causing significant graft versus host disease (GVHD). We previously demonstrated that these veto Tcm cells can effectively delete anti-donor T cell clones through a Fas-FasL mechanism, whereas their ability to neutralize alloreactive natural killer (NK) cells and the mechanism of such potential activity remained unknown. Using “nude” mice as recipients of allogeneic T cell-depleted hematopoietic stem cell transplantation (HSCT), we demonstrate effective inhibition of NK-mediated rejection by Tcm cells. Ex vivo studies revealed that Tcm cells express high levels of CD155, the ligand of the activating receptor DNAX accessory molecule-1 (DNAM-1). Conjugate formation between alloreactive NK cells and the veto cells induces NK anergy through a unique mechanism mediated by DNAM-1 internalization and degradation. These insights on veto Tcm cells and their impact on alloreactive NK cells offer potential translational approaches for haploidentical bone marrow transplantation and off-the-shelf chimeric antigen receptor (CAR) cell therapies.